Millisecond Conversion of Photovoltaic Silicon Waste to Binder‐Free High Silicon Content Nanowires Electrodes (Adv. Energy Mater. 40/2021). Issue 40 (27th October 2021) - Lu, Jijun; Liu, Siliang; Liu, Junhao; Qian, Guoyu; Wang, Dong; Gong, Xuzhong; Deng, Yida; Chen, Yanan; Wang, Zhi
Abstract : Waste to Electrodes In article number 2102103, Junhao Liu, Yanan Chen, Zhi Wang and co‐workers propose an electrothermal shock method that directly converts photovoltaic silicon waste to Si nanowire (SiNW) electrodes in milliseconds. The SiNW electrode has a Si content of 76% and exhibits an ultrahigh initial Coulombic efficiency (89.5%) and stable half/full cell cycle performance. Successful application of this method opens a new pathway for promotion of sustainable development of renewable energy.